Improving the nutritional performance of gluten-free pasta with potato peel autohydrolysis extract. (July 2020) - Fradinho, P.; Oliveira, A.; Domínguez, H.; Torres, M.D.; Sousa, I.; Raymundo, A.
Abstract: The potato processing industry produces peels, a good source of fibres, minerals and antioxidants, which could be recovered and used in the production of added-value products, such as gluten-free (GF) foods especially designed for the celiac population. This work is focused on the application of the bioactive fraction extracted from potato peels into GF pasta. Subcritical water extraction (autohydrolysis, AH) was performed on potato peel, and the obtained AH liquid extract was characterized in terms of total phenolic content and antioxidant activity. The selected AH temperature (220 °C at 2.2 MPa) was applied to peels from Kennebec, Neiker and Agria potato varieties, and the Agria extract was selected for application in GF pasta, as this was the one with higher antioxidant activity. The impact of Agria potato peel autohydrolysis extract on the nutritional composition and cooking quality of pasta was assessed. Results confirmed that the GF pasta enriched with potato peel extract presented suitable technological properties, coupled with attractive colour and with increased total phenolic content and antioxidant activity, which can contribute to improve the offer of GF products in the market. Highlights: Antioxidant rich extracts from potato peels were obtained by autohydrolysis. Potato peels from Agria variety showed high total phenolic content. Gluten-free pasta could bear a fat-free nutrition claim. Enriched gluten-free pasta showed high total phenolic content.